2003
DOI: 10.1002/humu.9187
|View full text |Cite
|
Sign up to set email alerts
|

Identification of twelve novel mutations in patients with classic and variant forms of maple syrup urine disease

Abstract: Maple syrup urine disease (MSUD) is an autosomal recessive metabolic disorder of panethnic distribution caused by a deficiency of the activity of branched-chain alpha-ketoacid dehydrogenase (BCKD) complex. Mutations in the human BCKD genes E1alpha (BCKDHA), E1beta (BCKDHB) and E2 (DBT) are known to result in MSUD, referred to as type Ia, Ib and II mutations respectively. In this study 16 patients with the classic severe form of MSUD and three patients with milder variant forms of the disease were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 21 publications
7
21
0
Order By: Relevance
“…Somatic cell complementation studies applied to the cell strains allowed their classification into the genetic subtypes Ia, Ib and II according to the gene presumable harboring the mutant alleles. The distribution observed, 15 /33 in the Ib subtype, 10 /33 in the Ia, 7/ 33 in the II and 1 with an ambiguous result is similar to that found in other studied populations (Henneke, et al, 2003;Nellis and Danner, 2001). No EIII genetic subtype strain has been detected in this cohort (data not shown).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Somatic cell complementation studies applied to the cell strains allowed their classification into the genetic subtypes Ia, Ib and II according to the gene presumable harboring the mutant alleles. The distribution observed, 15 /33 in the Ib subtype, 10 /33 in the Ia, 7/ 33 in the II and 1 with an ambiguous result is similar to that found in other studied populations (Henneke, et al, 2003;Nellis and Danner, 2001). No EIII genetic subtype strain has been detected in this cohort (data not shown).…”
Section: Resultssupporting
confidence: 86%
“…The c.487G>T change appears in homozygous fashion in three patients without consanguineous pedigree proved but all coming from the same Spanish geographic area. (Henneke, et al, 2003) DNA mutation numbering is based on cDNA reference sequence (GenBank Accession number NM_000056.2) considering nucleotide +1 as the A of the ATG translation initiation codon. Seven different variations have been found in the DBT gene.…”
Section: Mutation Detectionmentioning
confidence: 99%
“…Previous imaging studies in MSUD patients have shown signs of both diffuse edema and intense local edema during the acute phase of the disease (12,13). Early diagnosis is essential for the reversal of MSUD encephalopathy and delayed treatment can lead to death (14).…”
Section: Discussionmentioning
confidence: 99%
“…At present, control group size appears to be arbitrary, with 100 chromosomes being a popular choice (Colomb et al 2003;DiFonzo et al 2003;Eng et al 2003;Henneke et al 2003;Isidro et al 2003;Kramer et al 2003;Njalsson et al 2003;Royer et al 2003). Examination of the "Mutation in Brief" section of two recent issues of Human Mutation (volume 22, issues 6 and 7) revealed that eight of 11 mutation-detection experiments screened 100 or fewer control chromosomes for a putative disease-causing mutation that was initially found in a patient.…”
Section: ‫4מ‬mentioning
confidence: 99%